Pulse 2: China navigates its Covid-19 recovery - outward investment appetite and implications for developing countries - Beatrice Tanjangco; Yue Cao; Rebecca Nadin; Olena Borodyna; Linda Calabrese; Yunnan Chen (Overseas Development Institute (ODI), 2021)
This is the second report in ODI's Economic Pulse series. Pulse 2 explores China's international economic response as the world adapts to Covid-19. The report analyses China's international engagements, especially in developing countries, against the backdrop of its own recovery and a still difficult external trade environment. China will have to navigate its role in the new Covid-19 normal while balancing both growth and financial stability in its own recovery. It will also be balancing its domestic and international agendas as it pursues the `dual-circulation' strategy.
Keywords: 330; China; COVID-19; Economics; Economic growth